Coordinating Supply Chains with Simple Pricing Schemes: The Role of Vendor-Managed Inventories - Bernstein, Fernando; Chen, Fangruo; Federgruen, Awi (Management Science, 2006)
We characterize supply chain settings in which perfect coordination can be achieved with simple wholesale pricing schemes: either retailer-specific constant unit wholesale prices or retailer-specific volume discount schemes. We confine ourselves to two-echelon supply chains with a single supplier servicing a network of retailers who compete with each other by selecting sales quantities. We identify a key sufficient condition, in terms of interdependencies between chain members' operational decisions, under which perfect coordination via simple schemes is feasible, under general cost and demand functions. This condition, which we refer to as echelon operational autonomy (EOA), states that the costs incurred by the supplier for a given vector of sales volumes depends only on operational decisions she controls herself. At the same time, the costs incurred by the retailers may depend on operational decisions controlled by the supplier, in which case, the supplier's operational decisions are made to minimize chainwide costs. We show how vendor-managed inventory (VMI) partnerships create EOA and compare the resulting coordinating pricing schemes with those required in a traditional decentralized setting (without EOA). We also discuss compliance issues with the coordinating schemes in view of the Robinson-Patman act and provide remedies to overcome these issues.